Segregação socioespacial e saúde materno-infantil de mães adolescentes no município de Belo Horizonte - Mariana de Melo Santos (2019)
Introduction: Living in a context of socioeconomic disadvantage is associated with a higher risk of pregnancy in adolescence. However, there is controversy in the literature if worse outcomes for live births of adolescent mothers, such as preterm birth. and low birth weight, may not only be a consequence of the mother's biological immaturity, but also associated with socioeconomic and contextual factors. Socio-spatial segregation by income has been associated with disparities in maternal and child health. Objectives: To evaluate the association of neonatal outcomes of live births of adolescent mothers compared to those of adult mothers in the different contexts of socio-spatial segregation as measured by the Extreme Concentration Index (ICE) in the city of Belo Horizonte in 2012. Methods: This is a cross-sectional study with a sample of 16.562 live births of mothers between 12 and 29 years of age in 2012. The dependent variables were low birth weight and preterm birth. The independent variable was maternal age categorized into four age groups: 12 to 15 years, 16 to 19 years, 20 to 24 years, and 25 to 29 anos, the latter being used as a reference. Bivariate and logistic regression analyzes were performed, adjusted for the mother's race / color of skin, marital status, maternal education (apropriate for age), parity, prenatal care and type of delivery. Results: After all adjustments, in the areas with the highest concentration of socioeconomic deprivation (1st tertile of ICE), newborns of adolescent mothers aged 12 to 15 years presented higher odds of preterm birth (OR 2.37 [1.50 – 3.75]) and low birth weight, in relation to those of adult mothers (OR 1.82 [1.10 – 3.01]). In the 2nd tertile of ICE, the association remained statistically significant in the final model only for low birth weight, with children of adolescent mothers aged 12 to 15 years, who were more likely to have this outcome compared to adult mothers. In the areas with the highest concentration of socioeconomic privilege (3rd tertile of ICE), a greater odds of preterm birth was observed (OR 2.1 [1.16 – 3.79]) in the mothers of 12 to 15 years. Conclusion: Differences in neonatal outcomes in newborns of adolescent mothers, when compared to those of young adult mothers, may be influenced by factors that go beyond biological immaturity. In order to analyze these differences, the different socioeconomic contexts in which the mothers live must be taken into account.